Последний кабан из лесов Понтеведра: повести / Дина Рубина - Рубина Дина Ильинична (Эксмо, 2011)
Экземпляры: аб. (20161027) / Инвентарный номер: 57140 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: Р 82 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44